Forty Seventh Meeting of the National Development Council at Vigyan Bhavan, New Delhi on 16th January, 1997 Summary Record - Planning Commission (Planning Commission, 1997)
The National Development Council held its Forty Seventh Meeting at Vigyan Bhavan, New Delhi on 16th January, 1997 under the Chairmanship of Shri H.D. Deve Gowda, Prime Minister, and Chairman of the Council, to consider the draft Approach Paper to the Ninth Plan (1997-2002).
Government of India Planning Commission
Government of India Planning Commission